Keamanan Jaringan Pada Sistem Pakar Diagnosa Penyakit Ibu Hamil Menggunakan Metode Forward Chaining Dan Algoritma Affine Cipher (Studi Kasus Klinik Fatimah Medika - Fajar Yulian Siska Utama; Muchamad Kurniawan; Siti Agustini (Institut Teknologi Adhi Tama Surabaya, 2022)
Data security is the most important part of a system., particularly in supporting information security at institutions both public and private because it can guarantee the security of messages that will be given to the intended person or institution. Basically, data can be classified into public data and private data. Public data means data that can be accessed by many people, while private data can only be accessed by people who have access. Therefore, encryption is needed to keep the secrecy of data or information. Fatimah Medika Clinic is a heart clinic that servers treatment and health checks. The clinic, which is located at Terungkulon Road, Krian, Sidoarjo. In this final project, we discuss cryptography using the Affine Cipher algorithm. This algorithm is a development of Caesar algorithm using twho keys. This application could perform the encryption and decryption processes on patient data saved in the system. The retrieval of two keys in the Affine Cipher algorithm occurred automatically by taking the patien’s date and month of birth into account. The results of tests on 100 data sets in which each character had the size of 3 to 12 letters yielded an average Mean Square Error (MSE) value of 9,272 abd a Peak Signal to Noise Ratio (PSNR) value of 7,379. Accordingly, by implementing the Affine Cipher algorithm into the application, we can save information from anyone without it being readable by others.